MAKNA KONTEKSTUAL TEKURERU DAN TEYARU DALAM NOVEL BOTCHAN - Wiyatasari, Reny (Vocational College of Diponegoro University, 2017)
The problem in this research is the contextual meaning of tekureru and teyaru ( teageru) usage. This research is a descriptive case study on Japanese novel of Botchan which applied purposive sampling. The data were collected by employing observation method through note-taking techniques. The data were analysed by using componential analysis of Spradley.The result of research shows that : tekureru and teyaru ( teageru) have beneficial meaning and disadvantageous meaning. The supporting verb of tekureru have beneficial meaning and disadvantageous meaning beside thanking meaning.. The usage of supporting verb teyaru ( teageru) not only has beneficial meaning, but also have disadvantageous meaning when it’s usage give a bad influence on listener or on p.